Philosophos Plato's missing dialogue - Gill, Mary Louise, 1950- (Oxford : Oxford University Press, 2012)
This text presents a bold new explanation of why the dialogue which Plato promised to write on the Philosopher, complementing the Sophist and the Statesman, is missing. It argues that he left it unwritten in order to stimulate his readers and encourage them to work out, for themselves, the portrait it would have contained.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Plato